Surveillance and governance crime control and beyond - Deflem, Mathieu (Bingley, UK : Emerald/JAI, 2008)
This volume presents recent insights in the sociological study of surveillance and governance in the context of criminal justice and other control strategies. The chapters provide a varied set of theoretical perspectives and substantive research domains on the qualities and quantities of some of the most recent transformations of social control as well as their historical precursors in diverse social settings. The contributors to this volume testify to the increasing relevance of surveillance and governance across the globe as well as the cross-national study thereof. Among the central issues discussed is the relationship between state and non-state mechanisms of surveillance. Moreover, many of the new technologies that a decade ago led to analytical reflections of the highest order today have become banal in their everyday application and routine diffusion. What can sociologists intelligently say about these developments in both empirical and theoretical respects? Creatively exploring many facets of the broader constellation of contemporary surveillance and governance strategies with respect to both crime control and related developments, the contributors of this volume offer provocative and thoughtful reflections that will stimulate our theoretical thinking about relevant issues.This is a contemporary study of surveillance and governance. It includes contributions from an international group of leading scholars.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Electronic surveillance -- Social aspects; Electronics in crime prevention; Crime prevention -- Optical equipment; Closed-circuit television; Causes & prevention of crime; Social Science -- Criminology